Collective bargaining and human development: A capability approach to labor unionism in Polomolok, Southern Philippines - Estrera, Joseph Carl T; Vego, Eubert Martin F; Egot, Clifford Wyne D; Remegio, Diana Sophia M; Baran, Ernest; Lisbo, Kenneth Cantil (SIMULACRA: JURNAL SOSIOLOGI, 2025)
This study analyzed the impact of the Collective Bargaining Agreement (CBA) between Dole Philippines, Inc. and the Labor Employees Association of Dolefil Polomolok Hourlies (LEAD.PH) in South Cotabato, Southern Philippines on the development of workers' capabilities. It used Martha Nussbaum's Capability Approach (CA) framework. It examined how CA enhances employees' capabilities and functioning through economic security, health, education, and work-life balance. A mixed-methods approach was used, analyzing the 2020-2025 CBA and a phenomenological exploration of union members' lived experiences through semi-structured interviews. The results show that the CBA significantly improves health and work-life balance through benefits such as health care and leave entitlements. However, challenges remain in terms of economic stability, access to technical training, professional development opportunities, and wage structures that may not fully meet the evolving needs of the workforce. These constraints can affect workers' agency and their ability to enjoy the life they value. Despite these challenges, the study highlights the importance of incorporating comprehensive development into CBAs, addressing both the personal and professional needs of workers. This study underscores the need for CBAs to prioritize employees' well-being and skills development to ensure they have the opportunity to lead meaningful and fulfilling lives.